(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Neutron activation analysis and gamma-ray spectrometry was used to determine 238U, 226Ra, 228Ra, 210Pb, 232Th and 40K contents in feed pulverized coal, bottom ash, fly ash from cyclone and baghouse filters, zeolites synthesized from the ashes and two different soil samples. All the samples used in the study was collected at Figueira thermoelectric power plant, located in the city of Figueira, Paraná State, which coal presents a significant amount of uranium concentration. The natural radionuclide concentrations in pulverized coal were 4216 Bq kg–1 for 238U, 180 Bq kg–1 for 226Ra, 27 Bq kg–1 for 228Ra, 28 Bq kg–1 for 232Th and 192 Bq kg–1 for 40K. The ashes fraction presented concentrations ranging from 683.5 to 1479 Bq kg–1 for 238U, from 484 to 1086 Bq kg–1 for 226Ra, from 291 to 1891 Bq kg–1 for 210Pb, from 67 to 111 Bq kg–1for 228Ra, from 80 to 87 Bq kg–1 for 232Th and from 489 to 718 Bq kg–1 for 40K. Similar ranges were observed for zeolites. The activity concentration of 238U was higher than worldwide average concentration for all samples. The concentration of the uranium series found in the ashes were lower than the values observed in similar studies carried out 10 years ago and under the limit adopted by the Brazilian guideline (CNEN-NN-4.01). Nevertheless, the concentrations of this specific area are higher than others coal mines and thermoelectric power plants in and out of Brazil, so it is advisable to evaluate the environmental impact of the installation.